THEORY AND PRACTICE OF THE COMMUNIST CULTURAL ACTIVISM IN KERALA - John S. P. (REVIEW OF SOCIAL SCIENCES, 2014)
The emergence of the Left ideological currents in the world politics gave rise to serious debates about the role and importance of culture in political affairs. The cultural movements were then viewed as a way to attain cultural hegemony, which provides a platform to build political hegemony. The cultural programmes were also viewed as a tool to carry political propaganda for mobilizing the proletariat and other marginalized sections of the society. In this regard, the Leftist theoreticians made serious efforts in shaping a theoretical base to the cultural strategies. The present research paper assess and analyses the communist cultural theories and its intervention in the literary and theatre scenario of Kerala.